Access to Healthcare Interpreter Services: Where Are We and Where Do We Need to Go? - Bischoff, Alexander (Molecular Diversity Preservation International (MDPI), 2010)
Due to international migration, health care professionals in Switzerland increasingly encounter language barriers in communication with their patients. In order to examine health professionals’ attitudes and practices related to healthcare interpreting, we sent a self-administered questionnaire to heads of medical and nursing departments in public healthcare services in the canton of Basel-Stadt (N = 205, response rate 56%). Strategies used to communicate with foreign-language speaking patients differed, depending on the patient’s language. While nearly half of respondents relied on patients’ relatives to translate for Albanian, Tamil, Bosnian, Croatian, Serbian, Portuguese and Turkish, a third did so for Spanish, and a fourth did so for Arabic. Eleven percent relied on professional interpreters for Spanish and 31% did so for Tamil and Arabic. Variations in strategies used appear to mainly reflect the availability of bilingual staff members for the different languages. Future efforts should focus on sensitizing health professionals to the problems associated with use of ad hoc interpreters, as well as facilitating access to professional interpreters.